Revisiting Jaśkowski’s Criterion - Krawczyk, Jakub (Logic and Logical Philosophy, 2026)
This paper aims to re-examine the so-called Jaśkowski’s criterion. This guiding principle was initially proposed as a methodological instrument for delineating formal systems as either satisfactory or unsatisfactory paraconsistent logics. It is a historical fact that Jaśkowski’s criterion has been, and remains, frequently overlooked in the relevant literature. In order to provide a detailed explanation of this fact and the argument for it being a regrettable state, there are three main points elaborated upon. Firstly, the philosophical motivations of Jaśkowski’s work. Secondly, an overview of some early attempts of meeting requirements of Jaśkowski’s criterion. Thirdly, its relevance to contemporary research in the field of philosophical logic, particularly in relation to recent discussions on the notion of ‘philosophical interpretation’. From the above, philosophical conclusions are drawn, and avenues for further research are identified.